ROS self-scavenging polythiophene materials for cell imaging. Issue 48 (13th October 2015) - Hu, Rong; Wang, Fengyan; Li, Shengliang; Nie, Chenyao; Li, Meng; Chen, Hui; Liu, Libing; Lv, Fengting; Wang, Shu
Abstract : A conjugated polymer (PTDHP ) was synthesized which has a unique ROS self-scavenging ability through the oxidation of DHP into a pyridine structure upon light irradiation. Thus, PTDHP achieves cell imaging with good photo-stability and low photo-cytotoxicity. Abstract : A conjugated polymer (PTDHP ) was synthesized by modifying the side chain of cationic polythiophene (PT ) with a dihydropyridine (DHP) group via a click reaction.PTDHP has a unique ROS self-scavenging ability through the oxidation of the DHP into a pyridine structure upon light irradiation. Thus, PTDHP achieves cell imaging with good photo-stability and low photo-cytotoxicity.